Can Surgeon Demographic Factors Predict Postoperative Complication Rates After Elective Spinal Fusion?. Issue 2 (March 2018) - Chun, Danielle S.; Cook, Ralph W.; Weiner, Joseph A.; Schallmo, Michael S.; Barth, Kathryn A.; Singh, Sameer K.; Freshman, Ryan D.; Patel, Alpesh A.; Hsu, Wellington K.
Abstract : Study Design: Retrospective cohort. Objective: Determine whether surgeon demographic factors influence postoperative complication rates after elective spine fusion procedures. Background: Surgeon demographic factors have been shown to impact decision making in the management of degenerative disease of the lumbar spine. Complication rates are frequently reported outcome measurements used to evaluate surgical treatments, quality-of-care, and determine health care reimbursements. However, there are few studies investigating the association between surgeon demographic factors and complication outcomes after elective spine fusions. Methods: A database of US spine surgeons with corresponding postoperative complications data after elective spine fusions was compiled utilizing public data provided by the Centers for Medicare and Medicaid Services (2011–2013) and ProPublica Surgeon Scorecard (2009–2013). Demographic data for each surgeon was collected and consisted of: surgical specialty (orthopedic vs. neurosurgery), years in practice, practice setting (private vs. academic), type of medical degree (MD vs. DO), medical school location (United States vs. foreign), sex, and geographic region of practice. General linear mixed models using a Beta distribution with a logit link and pairwise comparison with post hoc Tukey-Kramer were used to assess the relationship between surgeon demographics and complication rates. Results: 2110 US-practicing spine surgeons who performed spine fusions on 125, 787 Medicare patients from 2011 to 2013 met inclusion criteria for this study. None of the surgeon demographic factors analyzed were found to significantly affect overall complication rates in lumbar (posterior approach) or cervical spine fusion. Conclusions: Publicly available complication rates for individual spine surgeons are being utilized by hospital systems and patients to assess aptitude and gauge expectations. The increasing demand for transparency will likely lead to emphasis of these statistics to improve outcomes. We conclude that none of the surgeon demographic factors analyzed in this study are associated with differences in overall complications rates in patients undergoing elective spine fusion as published by the ProPublica Surgeon Scorecard. Level of Evidence: Level 3.